A dopamine electrochemical sensor based on gold nanoparticles/over-oxidized polypyrrole nanotube composite arrays1. Issue 13 (14th February 2015) - Lin, Meng
<x xml:space="preserve">Abstract</x> A novel sensor based on a gold nanoparticles (Au NPs)/over-oxidized polypyrrole (OPPy) nanotube (NT) composite array electrode proved to be highly effective for electrochemical determination of dopamine (DA).